Data Colonialism: Rethinking Big Data's Relation to the Contemporary Subject. (May 2019) - Couldry, Nick; Mejias, Ulises A.
We are often told that data are the new oil. But unlike oil, data are not a substance found in nature. It must be appropriated. The capture and processing of social data unfolds through a process we call data relations, which ensures the "natural" conversion of daily life into a data stream. The result is nothing less than a new social order, based on continuous tracking, and offering unprecedented new opportunities for social discrimination and behavioral influence. We propose that this process is best understood through the history of colonialism. Thus, data relations enact a new form of data colonialism, normalizing the exploitation of human beings through data, just as historic colonialism appropriated territory and resources and ruled subjects for profit. Data colonialism paves the way for a new stage of capitalism whose outlines we only glimpse: the capitalization of life without limit.